2003
DOI: 10.1021/jo034526o
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Pericyclic and Pseudopericyclic Thermal Cheletropic Decarbonylations. Evaluation of Magnetic Properties

Abstract: A comprehensive B3LYP/6-31G** study of various thermal cheletropic decarbonylations was conducted. The complete pathway for each reaction was determined, and changes in magnetic susceptibility and its anisotropy were monitored with a view to estimating the aromatization associated to each process. This information, together with the energy and structural results, allowed us to clarify cases that are not clearly pseudopericyclic or pericyclic from previous work. Also, our results reveal that pericyclic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Later many methods based on the magnetic properties such as NICS, 7,8 ACID 9-12 have been developed to characterize pseudeopericyclic reactions. These methods were successfully used by Rodrίguez Otero and their coworkers, [13][14][15][16][17][18][19] to identify the nature of reactions as pericyclic or pseudopericyclic. Lopez and de Lera et al 20 showed that pseudopericyclic reactions do not show a maximum in ellipticity of the forming bond along the reaction coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…Later many methods based on the magnetic properties such as NICS, 7,8 ACID 9-12 have been developed to characterize pseudeopericyclic reactions. These methods were successfully used by Rodrίguez Otero and their coworkers, [13][14][15][16][17][18][19] to identify the nature of reactions as pericyclic or pseudopericyclic. Lopez and de Lera et al 20 showed that pseudopericyclic reactions do not show a maximum in ellipticity of the forming bond along the reaction coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Pseudopericyclic transition states exhibit a disconnection in their otherwise cyclic system of delocalized electrons. 36 In ACID plots this is nicely reflected by a disconnection in the ACID surface.…”
Section: Acid Calculationsmentioning
confidence: 99%
“…During our continuous interest in the construction of large π systems , we developed the cheletropic cycloreversion expelling carbon monooxide in the fusion of π systems yielding very large π compounds as well as the retro‐Diels–Alder protocol . Among the pericyclic cycloreversion reactions, cheletropic degradation reactions extruding carbon mono‐oxide are the most advantageous, even if the target π systems are reactive and labile . We have successfully utilized the reactions for construction of acene derivatives such as naphthacenes , pentacenes , and an anthracene‐fused pyrrole .…”
Section: Introductionmentioning
confidence: 99%